Reintegrating Filipino migrant teachers an exploratory study - Sabado, Ma. Cynthia Limson (2007)
This research aimed to determine the needs of Filipino migrant teachers in reintegration, and to identify which of these need to be addressed in the long-term and short-term reintegration programs. Primary data were gathered from personal interviews and questionnaires answered by teachers who are currently teaching abroad and those who returned. Secondary data were obtained from family members left behind and field observation in POEA and OWWA programs. Research showed that financial motivation and international exposure satisfied the teachers migration objectives except for a few who returned. Migration will continue for teaching professionals in English, Math, and Special Education. DepEd and CHED ought to collaborate with OWWA to establish a job network in a shared website to facilitate job re-entries for academic personnel.
"March 2007."
Thesis (M.A. Educational Administration)--University of the Philippines Diliman.
Keywords: Teachers -- Employment -- Philippines